Bandung, laboratory for modern building in the latter days of the colonial era (Bulletin KNOB, 1989)
Next to Chinese and Indonesian inhabitants more than half of the population consisting of Europeans, Bandung (1900) used to be the most European town of the Dutch East Indies, her lay-out and architecture comparable with some of the Dutch garden cities. The immense growth of the population and traffic during the last decades as well as municipal priorities on social housing and hygienic provisions very much affected Bandung's original lay-out.Although present-day Indonesia knows a growing interest in the historic town and the built cultural heritage among municipalities and private persons, commercial pressure on the city-centre and especially the absence of rules on the field of urban development threaten the survival of the central area. In 1988 the RUDS-MBA project (Review Urban Development Strategy for the Bandung Metropolitan Area) has been started, evaluating previous plans and making recommendations for Bandung's development till 2006.Next to this project background studies have been executed on the request of the Ministry of Public Works. The 'Cultural Environment background study' represents a first stock-taking of valuable buildings and the signalizing of special areas of the historic urban structure in coherence with present-day functional developments. The stock-taking of the buildings resulted in a card-index with data of about 130 buildings.As typical example of the development of modern architecture between both World Wars, Bandung hardly possesses any 19th century architecture (some neoclassicist buildings excluded). The official as well as the villa-architecture from the first decades of this country has been raised in an eclectic romantic style, which strongly refers to contemporary currents in Holland. The improved infrastructure of the roads and especially the transference of public institutions from Batavia to Bandung caused an explosive growth of the town.During this short period of the Interbellum Bandung got her own identity. Unlike Western modern architecture these extension plans were determined by Indonesian conditions and available materials. The Bandung architects f.e. had to consider climatological factors like possible light earthquakes and high temperature. The decoration carried out by Chinese and Indonesian craftsmen represents a specific eastern approach, architecture and details thus marking the development to a mingled Indo-European architecture.